The unseen perils of oral-care products generated micro/nanoplastics on human health - Utsa Saha; Snehasmita Jena; Faizan Zarreen Simnani; Dibyangshee Singh; Anmol Choudhury; Shaikh Sheeran Naser; Sudakshya S. Lenka; Apoorv Kirti; Aditya Nandi; Adrija Sinha; Swadheena Patro; Małgorzata Kujawska; et al. (Ecotoxicology and Environmental Safety)
The extensive use of plastics in modern dentistry, including oral care products and dental materials, has raised significant concerns due to the increasing evidence of potential harm to human health and the environment caused by the unintentional release of microplastics (MPs) and nanoplastics (NPs). Particles from sources like toothpaste, toothbrushes, orthodontic implants, and denture materials are generated through mechanical friction, pH changes, and thermal fluctuations. These processes cause surface stress, weaken material integrity, and induce wear, posing health risks such as exposure to harmful monomers and additives, while contributing to environmental contamination. MPs/NPs released during dental procedures can be ingested, leading to immune suppression, tissue fibrosis, and systemic toxicities. The gut epithelium absorbs some particles, while others are excreted, entering ecosystems, accumulating through the food chain, and causing ecological damage. Although analytical techniques have advanced in detecting MPs/NPs in oral care products, more robust methods are needed to understand their release mechanisms. This review explores the prevalence of MPs/NPs in dentistry, the mechanisms by which MPs/NPs are released into the oral environment, and their implications for human and ecological health. It underscores the urgency of public awareness and sustainable dental practices to mitigate these risks and promote environmental well-being.